Anda di halaman 1dari 11

1

DETERMINANTS

DETERMINANTS
2.1

Basic Concepts
The eliminant of the variables from the equations
(i)

a1x + b1y = 0, a2x + b2y = 0


a1 b1
a2 b 2

is

(ii)

a1x + b1y + c1z = 0, a2x + b2y + c2z = 0 is


a1 b1 c1

= a1b2 a2b1 = D

a3x + b3y + c3z = 0, a2 b2 c 2 = D


a3 b3 c 3

Expansion w.r.t. first row.


b

a1 b2 c 2 b1 a2 c 2 + c1 a2 b 2 = a1 (b2c3 b3c2) b1(a2c3 a3c2) + c1 (a2b3 a3b2)


3
3
3
3
3
3
Expansion w.r.t. first column.
b

a1 b2 c 2 a2 b 1 c 1 + a3 b 1 c 1 = a1 (b2c3 b3c2) a2 (b1c3 b3c1) + a3 (b1c2 b2c1)


3
3
3
3
2
2
If you compare term by term you will observe that the two expansions are same.
2.2

Properties Of Determinant
1.

The value of determinant is not altered by changing rows into columns and columns into rows.

2.

If any two adjacent rows or two adjacent columns of a determinate are interchanged, the
determinant retains its absolute value but changes its sign.

3.

If any line of a determinant D be passed over p parallel lines the resultant determinate is (1)p D.

4.

If any two rows or two columns of a determinant are identical, then the determinant vanishes.

5.

If each constituent in any row or in any column be multiplied by the same factor then the
determinant is multiplied by that factor.

6.

If each constituent in any row or column consists of r terms then the determinant can be
expressed as the sum of r determinants.

7.

If to or from each constituent of a row (or column) of a determinant are added or subtracted the
equi-multiples of the corresponding constituent of any other row (or column) the determinant
remains unaltered.

(a)

The value of a determinant is obtained by multiplying the elements of any row (or column) with
the corresponding cofactors and adding the resulting products.

(b)

If we multiply the elements of any row (or column) with the corresponding cofactors of any other
row (or column) and add them, then the result is zero.

www.thinkiit.in

DETERMINANTS
(c)

If D is the determinant formed by replacing the elements of a determinant D by their


corresponding cofactors, then D = D2.

2.3

Special Determinants :
a h g

(1)

Symmetric determinant. hg bf cf = abc + 2fgh af2 bg2 ch2


In this the elements aij = aji or the elements situated at equal distance from the diagonal are equal
both in magnitude and sign.

(2)

-c
a
-a 0
b

Skew symmetric determinant of odd order. - b 0


c

= 0.

All the diagonal elements are zero and aij = aji or the elements situated at equal distance from
the diagonal are equal in magnitude but opposite in sign. Its value is zero.
a b c

(3)

Circulant b c a = (a3 + b3 + c3 3abc)


c a b

The three rows or columns are the cyclic arrangement of the letters a, b, c, i.e. a, b, c ; b,
c, a and c, a, b respectively.
(4)

Factors of three important determinants :

(i)

1 1 1
a b c
a2 b2 c 2

1 1
b c
a3 b3 c 3

(ii) a

= (a b) (b c) (c a)

=(a b) (b c) (c a) (a + b + c)

(iii) a2 b2 c 2 = (a b) (b c) (c a) (ab + bc + ca)


a3 b3 c 3

www.thinkiit.in

DETERMINANTS

SOLVED PROBLESM
x

sin cos
-x
1
cos
1
x

is independent of q.

Ex.1

Prove that the determinant -sin

Sol.

We shall expand this determinant, using Sarrus Method.


x

sin q

cos q

sin q

sin q

sin q

cos q

cos q

Thus, D = (x + sin q cos q sin q cos q) (x cos q + x x sin q) = x


Hence, the determinant is independent of q.

Ex.2

Evaluate :
1

(i) 1 x + y

Sol.

(i)

Let

y
y
x+y

(ii)

x
y
x+y

y
x+y
x

x+y
x
y

y
y
x+y

D = 1 x+y

Expanding it along the first column, we have


D=1

x+y
y
x
x+y

1 x x+y + 1 x+y y

= [(x + y) xy] [x (x + y) xy] + [xy xy y ]


2

= x + y + xy x y = xy

(ii)

Let

x
y
x+y
y
x+y
x
x+y
x
y

D=

=x

x+y x
x
y

x+y
x

y x + y y + (x + y) x + y

= x (xy + y x ) y (y x xy) + (x + y) (xy x y 2xy)


2

= x y + xy x y + x y + xy + x y x xy 2x y + xy x y y 2xy
3

= 2x 2y = 2 (x + y )

www.thinkiit.in

DETERMINANTS

Ex.3

Solve the equation

Sol.

Let

D=

x+
x
x
x
x+
x
x
x
x+

= 0, (a 0).

x+a
x
x
x
x+a
x
x
x
x+a

= (x + a)

x+a
x
x
x+a
2

x xx x +x a + x xx x +x a
2

= (x + a) [(x + a) x ] x [x (x + a) x ] + x [x x (x + a)]
3
2
2
2
= (x + a) x (x + a) ax ax
3
3
2
= (x + a) x 3ax
3
2
2
3
3
2
= x + 3ax + 3a x + a x 3ax
2
3
= 3a x + a
Equating it to zero, we have
2

3a x + a = 0

Ex.4

x=

a
3

If a, b and c are real numbers, and

D=

b+c c+a a+ b
c+a a+b b+c
a+ b b+c c+a

=0

Show that either a + b + c = 0 or a = b = c


Sol.

Here,

2 (a + b + c ) c + a a + b

D = 2 (a + b + c ) a + b b + c

2 (a + b + c ) b + c c + a

(C1 C1 + C2 + C3)

1 c +a a+b

= 2 (a + b + c) 1 a + b b + c

1 b+c c+a
1 c +a a +b

= 2 (a + b + c) 0 b - c c - a
0 b-a c -b

(R2 R2 R1; R3 R3 R1)

b-c c -a

= 2 (a + b + c) 1 b - a c - b

= 2 (a + b + c) [(b c) (c b) (b a) (c a)]
2
2
2
= 2 (a + b + c) [bc c b + bc bc + ac + ab a ]
2
2
2
= 2 (a + b + c) (ab + bc + ca a b c )
Equating D to zero, we have
2
2
2
2 (a + b + c) (ab + bc + ca a b c ) = 0
2
2
2

Either a + b + c = 0 or ab + bc + ca = a + b + c

Either a + b + c = 0 or a = b = c

www.thinkiit.in

Ex.5

Sol.

DETERMINANTS

Show that

2 +
2 +
2 +

D=

a a2 b + g
b b2 g + a
g g2 a + b

Let

= (b g) (g a) (a b ) (a + b + g)

a - b a 2 - b2 b - a
b - g b2 - g 2 g - b
g
g2
a+b

1 a+b

-1
-1
a+b

= (a b) (b g) 1 b + g
g

(R1 R1 R2; R2 R2 R3)

= (a b) (b g)

0
a + b -1
0
b + g -1
a + b + g g2 a + b

(C1 C1 + C3)

= (a b) (b g) (a + b + g) ab ++ bg -- 11
= (a b) (b g) (a + b + g) (a b + b + g) = (a b) (b g) (g a) (a + b + g)

3a

-a + b -a + c
3b
-b + c
-c + a -c + b
3c

Ex.6

Show that -b + a

Sol.

Using C1 C1 + C2 + C3, we have

= 3 (a + b + c) (ab + bc + ca)

a+b+c -a+b -a+c


3b
-b+c
a+b+c -c+b
3c

D = a+b+c

1 -a+b -a+c
3b
-b+c
1 -c +b
3c

= (a + b + c) 1

1 -a+b -a +c
a-b
0 a - c a + 2c

(R2 R2 R1; R3 R3 R1)

= (a + b + c) 0 a + 2b

= (a + b + c) 1. aa+-2cb aa+-2bc = (a + b + c) [(a + 2b) (a + 2c) (a b) (a c)]


= (a + b + c) (3ab + 3bc + 3ca) = 3 (a + b + c) (ab + bc + ca)

1+ p

1+ p + q

Ex.7

Prove that 2 3 + 2p 4 + 3p + 2q = 1

Sol.

Let

3 6 + 3p 10 + 6p + 3q

1+ p

1+ p + q

1 1+ p 1 + p + q
1
2+p
0 3
7 + 3p

D = 2 3 + 2p 4 + 3p + 2q = 0
3 6 + 3p 10 + 6p + 3q

(R2 R2 R1; R3 R3 R1)

2+p

= 3 7 + 3p = (7 + 3p) 3(2 + P) = 1
Ex.8

x + 2 x + 3 x + 2a

If a, b, c are in AP, prove that : x + 3 x + 4 x + 2b = 0


x+4 x+5

x + 2c

www.thinkiit.in

6
Sol.

DETERMINANTS
Let

x + 2 x + 3 x + 2a

D = x + 3 x + 4 x + 2b
x + 4 x + 5 x + 2c

x + 2 x + 3 x + 2a
1
1
2(b - a)
2
2
2(c - a)

x+2 x+3
x + 2a
1
1
2(b - a)
0
0
2(c - a) - 4(b - a)

(R2 R2 R1; R3 R3 R1)

(R3 R3 2r2)

= [2 (c a) 4 (b a)] x +1 2 x +1 3
= [2c 2a 4b + 4a] (x + 2 x 3)
= [2c + 2a 4b] (1) = (4b 2a 2c)
Since, a, b, c are in AP,
2b = a + c
\
4b = 2a + 2c
Hence by (1), D = 0
(b + c)2
a2
a2
2
2
b
(c + a)
b2
2
2
c
c
(a + b)2

Ex.9

Prove that

Sol.

Replacing C2 by C2 C1 and C3 by C3 C1, we have


D

= 2abc (a + b + c)

(....1)

(b + c )2 a2 - (b + c )2 a2 - (b + c )2
b2
(c + a)2 - b2
0
2
c
0
(a + b)2 - c 2

b2 + c 2 + 2bc a - b - c a - b - c
b2
c + a-b
0
c2
0
a+b-c

Replacing R1 by R1 R2 R3, we have


2

D = (a + b + c)

Replacing C2 by C3 +

1
b

2bc
- 2c
- 2b
b2 c + a - b
0
c2
0
a+b-c

C1 and C3 by C3 +

D = (a + b + c)

2bc

b2

c+a

c2

c2
b

1
c

C1, we have

0
b2
c
a+b

= 2bc (a + b + c) [(a + c) (a + b) bc]


2 2
= 2bc (a + b + c) (a + ab + bc bc)
3
= 2abc (a + b + c)

www.thinkiit.in

(a

c)

7
DETERMINANTS
Ex.10 Find the values of h if area of a triangle is 4 sq. units and vertices are (i) (k, 0) (4, 0) (0, 2)
Sol.

(i)

The area of the triangle =

1 k 0 1
4 0 1
2 0 2 1

1
2

[k (0 2) 0(4 0) + 1(8 0)]

1
2

(2k + 8) = (4 k) sq units

According to the question,


4k=4
or
4 k = 4

k=0
k=8
Hence, the possible values of k are 0 and 8.
(ii)

Area of the triangle =

1 -2 0 1
0 4 1
2 0 k 1

1
2

[2 (4 k) 0 (0 0) + 1 (0 0)]

= (k 4) sq units
According to the question,
k4=4
or
k 4 = 4

k=8
k=0
Hence, the possible values of k are 8 and 0.
Ex.11 Using determinants, find the equation of the line AB, joining
(i)
A (1, 2) and B (3, 6)
(ii)
A (3, 1) and B (9, 3)
Sol. Let P (x, y) be any point on AB. Then, area of the triangle ABP is zero, since the points A, B and P are
collinear. So,
(i)

1 1 2 1
3 6 1
2 x y 1
1
2

=0

[1 (6 y) 2(3 x) + 1(3y 6x)] = 0

6 y 6 + 2x + 3y 6x = 0

y = 2x
Hence, the equation of the line AB is y = 2x.
(ii)

1 3 1 1
9 3 1
2 x y 1
1
2

=0

[3 (3 y) 1(9 x) + 1(9y 3x)] = 0

9 3y 9 + x + 9y 3x = 0

2x = 6y

x = 3y
Hence, the equation of the line AB is x = 3y.

www.thinkiit.in

DETERMINANTS

UNSOLVED PROBLEMS
EXERCISE I
Q.1
Q.2

Q.3

2 5

4 - 3

If A = 2 1 and B = 2 5 , verify that |AB| = |A| |B|


Without expanding evaluate the determinant

b2c 2 bc b + c
c 2a2 ca c + a
a2b2 ab a + b

Without expanding evaluate the determinant

1 a a2 - bc
1 b b2 - ac
1 c c 2 - ab

(a x - a - x )2 (a x - a - x )2 1
(a y + a - y )2 (a y - a - y )2 1
(a2 + a - z )2 (a z - a -z )2 1

Q.4

Without expanding evaluate the determinant

Q.5

Without expanding evaluate the determinant sin b cos b sin( b + d)

Q.6

Prove that

1+ a
1
1
1 1+ b
1
1
1 1+ c

Q.7

Prove that

a + b + 2c
a
b
c
b + c + 2a
b
c
a
c + a + 2b

Prove that

(b + c )2 a2 bc
(c + a)2 b 2 ca
(a + b)2 c 2 ab

Q.9

Show that

1 + a2 - b2
2ab
- 2ab
2ab
1 - a2 + b2
2a
2b
1 - a2 - b2
- 2a

Q.10

Solve :

Q.8

sin a cos a sin( a + d)


sin g cos g

3x - 8
3
3
3
3x - 8
3
3
3
3x - 8
x x 2 1 + x3
y y 2 1 + y3
z z2 1 + z3

sin( g + d)

1 1 1
= abc 1 1 + + + = abc + ab + bc + ca

= 2(a + b + c)3

= (a2 + b2 + c2) (a + b + c) (b c) (c a) (a b)

= (1 + a2 + b2)2

=0

Q.11

If x y z and

Q.12

If a, b, c are all positive and are pth, qth and rth terms respectively of a G.P. then prove that log b q 1

= 0, then prove that 1 + xyz = 0


log a p 1
log c r 1

=0
Q.13

Find the area of a triangle with vertices : (3, 5), (3, 6), (7, 2)

Q.14

Find the value of l so that the points given below are collinear (l, 2 2l), (l + 1, 2l) and (4, l, 6
2l)

Q.15

Using determinants, find the area of the triangle, whose vertices are (2, 4), (2, 6) and (5, 4). Are the
given points collinear ?

www.thinkiit.in

DETERMINANTS

BOARD PROBLES
EXERCISE II
Q.1

Prove

1 x x3
1 y y3
1 z z3

= (x y) (y z) (z x) (x + y + z).

Q.2

Prove using properties of determinants

Q.3

Prove using properties of determinants


(a)

Q.4

= 0.

[C.B.S.E. 2001]
[C.B.S.E. 2002]

= (x y) (y z) (z x).

(b)

x+y
x x
5 x + 4y 4 x 2x
10 x + 8 y 8x 3 x

Using the properties of determinants, show that


(a)

Q.5

1 x + y x2 + y2
1 y + z y 2 + z2
1 z + x z2 + x 2

b2c 2 bc b + c
c 2a2 ca c + a
a2b2 ab a + b

[C.B.S.E. 2000]

43 3 6
35 21 4
17 9 2

[C.B.S.E. 2002]

= 0.

(b)

9 9 12
1 3 -4
1 9 12

Using the properties of determinants, show that


(a)

a+x
y
z
x
a+y
z
x
y
a+z

= x3.

[C.B.S.E. 2003]

= a (a + x + y + z).

(b)

0 ab 2 ac 2
a2b 0 bc 2
a2c cb2 0

y+z
z
y
z
z+x
x
y
x
x+y

Q.6

Using the properties of determinants, prove that

Q.7

Using the properties of determinants, solve for x a - x a + x a - x = 0.

Q.8

Show that x + 2 x + 3 x + b = 0 where a, b and c are in A.P..

[C.B.S.E. 2005]

Q.9

Using the properties of determinants, prove that

[C.B.S.E. 2005]

Q.10

x+a a-x a-x

a-x a-x a+x

x +1 x + 2 x + a

x+3 x+4 x+c

(a)

1 1 1
a b c
a3 b3 c 3

(b)

x
y
z
x2
y2
z2
y+z z+x x+y

= 4xyz

[C.B.S.E. 2004]

[C.B.S.E. 2005]

= (a b) (b c) (c a) (a + b + c)

= (x y) (y z) (z x) (x + y + z).
x +1 x + 2 x + a

If a, b and c are in A.P., show that x + 2 x + 3 x + b = 0


x+3 x+4 x+c

www.thinkiit.in

[C.B.S.E. 2006]

10
Q.11

DETERMINANTS
Using the properties of determinants, prove that
b+c c+a a+b
q+r r +p p+q
y+z z+x x+y

(a)

Q.12

a b c

=2 p q r

[C.B.S.E. 2006]
3a - a + b - a + c
a-b
3b
c -b
a-c b-c
3c

(b)

x y z

= 3(a + b + c) (ab + bc + ca)

Using the properties of determinants, prove that

1 bc bc(b + c )
1 ca ca(c + a)
1 ab ab(a + b)

(a)

[C.B.S.E. 2007]
x x2 yz
y y2 zx
z z2 xy

= (x y) (y z) (z x) (xy + yz + zx)

= 0, show that xyz = 1.

[C.B.S.E. 2008]

= 0.

(b)

x x 2 1 + x3
y y 2 1 + y3
z z2 1 + z3

Q.13

If x, y, z are different and

Q.14

If a, b and c are all positive and distinct, show that D = b c a has a negative value.

a b c

c a b

[C.B.S.E. 2008]
3x - 8
3
3
3
3x - 8
3
3
3
3x - 8

Q.15

Solve for x :

Q.16

Using the properties of determinants.

Q.17

= 0.

(a)

x x 2 1 + ax 3
y y 2 1 + ay 3
z z 2 1 + az 3

(b)

1 + a2 - b 2
2ab
- 2b
2ab
1 - a2 + b2
2a
2b
1 - a2 - b2
- 2a

(c)

1 x x2
x2 1 x
x x2 1

[C.B.S.E. 2008]

[C.B.S.E. 2008]

= (1 + axyz) (x y) (y z) (z x)

= (1 x )

3 2

= (1 + a2 + b2)3

(d)

1 a2 + bc a3
1 b2 + ca b3
1 c 2 + ab c 3

= (a b) (b c) (c a) (a2 + b2 + c2).

Using properties of determinants, prove the following :


[C.B.S.E. 2009]
(a)

1 + a2 - b2
2ab
- 2b
2ab
1 - a2 + b2
2a
2b
1 - a2 - b2
- 2a

1+ p

1+ p + q

2 3

a2 + 1 ab
ac
ba b2 + 1 bc
ca
cb c 2 + 1
a

(c) 2 3 + 2p 1 + 3p + 2q = 1
3 6 + 3p 1 + 6p + 3q

= (1 + a + b ) (b)
2

= 1 + a2 + b2 + c2

(d) a - b b - c c - a = a3 + b3 + c3 3abc
b+c c +a a+b

www.thinkiit.in

11
Q.18

Q.19

DETERMINANTS
Using properties of determinants, prove the following :
(a)

(b + c )2
ab
ca
ab
(a + c )2
bc
ac
bc
(a + b)2

(b)

a + b + 2c
a
b
c
b + c + 2a
b
c
a
c + a + 2b

[C.B.S.E. 2010]

= 2abc (a + b + c)3

= 2 (a + b + c)3

[C.B.S.E. 2010]

Using properties of determinants, solve the following for x :


x-2
x-4

2x - 3
2x - 9

3x - 4
3 x - 16

x - 8 2x - 27 3x - 64

[C.B.S.E. 2011]

=0
b+c
a
a
b
c+a
b
c
c
a+b

Q.20

Using properties of determinants, show that

Q.21

Using properties of determinants prove the following :


x
x + 2y

x+y
x

x + 2y
x+y

x+y

x + 2y

[C.B.S.E. 2012]
[C.B.S.E. 2013]

= y2(x + y)

ANSWER KEY
EXERCISE 1 (UNSOLVED PROBLEMS)
2. 0
10. x =

3. 0

4. 0

5. 0

11 11 2
, ,
3
3 3

13. 46 sq. unit 14. l =

1
, 1
2

15. 35 sq. units, No

EXERCISE 2 (BOARD PROBLEMS)


4. (b) 576

3 3 3

5. (b) 2a b c

7. 0 or 3a

15.

2
3

or

11
3

www.thinkiit.in